Financial Inclusion and Poverty: Evidence From Turkish Household Survey Data - Dogan, Eyup; Madaleno, Mara; Taskin, Dilvin (Routledge Journals, Taylor & Francis Ltd, 2021)
Even though poverty is highly felt in developing economies, the lack of relevant and complete micro-level data limits understanding which households are more exposed to poverty and the role of financial inclusion in poverty in these countries. This research analyzes the effects of financial inclusion proxied by a multidimensional index on three poverty measures (the lowest-income poverty line, a lower-middle-income line, and an upper-middle-income line) by employing the recent Turkish Household Budget and Consumption Expenditure Survey data with 11,595 complete answers. In addition to the application of logistic regressions, this study addresses possible endogeneity issues by using access to the nearest bank as an instrument in a two-stage least-squares regression and employing the novel method as a robustness check. Empirical results point out that an increase in financial inclusion decreases poverty in Turkey. The adverse effect of financial inclusion on poverty is validated through a few robustness and sensitivity analyses. The outcome also indicates that health expenditure and income are essential through which poverty is influenced by financial inclusion. Thus, policies are required to enhance the financial inclusion of households to alleviate poverty. Further discussions are presented in this study.
Madaleno, Mara/0000-0002-4905-2771; Taskin, Dilvin/0000-0001-6139-8006; Dogan, Eyup/0000-0003-0476-5177
Keywords: Poverty; Financial Inclusion; Endogeneity; Turkey